PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI DINAS KELAUTAN DAN PERIKANAN KABUPATEN MESUJI - Jamal Jamal; I Komang Adi Candra (e-JKPP, 2018)
The problem lifted in this research is discipline work officer of The Office of Marine and Fisheries in Mesuji Regency. This research aim to lay open (1) influence of organization culture to discipline work officer, (2) influence of leadership style to discipline work officer, (3) Influence of organization culture and leadership style by together to discipline work officer. This research uses explanatory survey method. The population of this research are all officer of the Office of Marine and Fisheries in Mesuji Regency. Sample in this research entire/all from population that is as much 39 people. This Research consist of 3 (three) variables namely : organization culture (X1) and leadership style (X2) as independent variables and discipline work officer (Y) as a dependent variables. Result of analysis indicated that there are organization culture contribution to discipline work officer, contribution of leadership style to discipline work officer, and while organization culture contribution and leadership style concurrently to discipline work officer. The result of this reseach indicates that there is a positive influence and significant of organization culture toward discipline work officer, there is a positive influence and significant of leadership style toward discipline work officer, there is also a multiple positive influence and significant of organization culture and leadership style toward discipline work officer of The Office of Marine and Fisheries in Mesuji Regency. In an effort to improve the discipline work officer in the Office of Marine and Fisheries in Mesuji Regency need an increase in the quality of organization culture and leadership style. The higher the quality of organization culture and leadership style in the Office of Marine and Fisheries in Mesuji Regency the higher the quality of discipline work officer.